2009
DOI: 10.1021/jf803387z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dihydrogalangal Acetate in Galangal [Alpinia galangal (L.) Swartz] Extracts

Abstract: Dihydrogalangal acetate has been discovered for the first time in galangal roots [Alpinia galangal (L.) Swartz]. The compound has a taste sensation similar to galangal acetatethe pungent principle of galangalbut it is more stable in food and beverage applications. Therefore, dihydrogalangal acetate provides many advantages as a flavor ingredient for alcohol enhancement and taste modification. Dihydrogalangal acetate is present in approximately 0.0005% of fresh roots and in about 0.004% of dried roots. (S)-Dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The present results were consistent with previous studies indicating that MeOH and CH 2 Cl 2 extractable of Alpinia possess significant cytotoxicity against CORL23 human large-cell carcinoma with IC 50 values of 13.3 and 5.4 μg/ml respectively [48]. xPresent data were also consistent with previous studies indicating that galangal rhizomes and its ingredients possess cytotoxcity and free radical scavenging activities [54,55]. Phytochemical studies showed that of the many chemical constituents isolated from Alpinia, diaryheptanods, are among the characteristic compounds [56].…”
Section: Discussionsupporting
confidence: 92%
“…The present results were consistent with previous studies indicating that MeOH and CH 2 Cl 2 extractable of Alpinia possess significant cytotoxicity against CORL23 human large-cell carcinoma with IC 50 values of 13.3 and 5.4 μg/ml respectively [48]. xPresent data were also consistent with previous studies indicating that galangal rhizomes and its ingredients possess cytotoxcity and free radical scavenging activities [54,55]. Phytochemical studies showed that of the many chemical constituents isolated from Alpinia, diaryheptanods, are among the characteristic compounds [56].…”
Section: Discussionsupporting
confidence: 92%
“…To obtain a larger amount of this spicy “Wasabi‐like constituent,” the method of Yang and others () was followed. The cold EtAc extract (30 g) was fed onto the preparative adsorption column (100 × 50 mm i.d.)…”
Section: Methodsmentioning
confidence: 99%
“…• Dihydrogalangal acetate : 5 mg/kg in galangal roots (Yang et al, 2009) The remaining six substances (3,.080], 2-isopropyl-5-methylphenyl formate …”
Section: Natural Occurrence In Foodmentioning
confidence: 99%